FEM of Temperature Field of Rolling-sliding Compound Bearing - Lu Liming; Zeng Guowen (Jixie chuandong)
Taking the slide block of rolling-sliding compound bearing as a research object,a local heat transfer model is set up for rolling-sliding compound bearing between slide block and inner and outer raceway and cylinder.The contact surface temperature distribution between slide block and inner,outer raceway is analyzed by using the structure thermal- stress coupling effect of the finite element software ABAQUS.The temperature distribution characteristic of the rolling-sliding compound bearing under different revolving speed and radial load conditions are obtained.The results show that,the contact surface temperature between slide block and inner,outer raceway rising with the increasing of load and rotating speed.There is large difference in the temperature of various nodes on the contact surface of slide block with inner and outer raceway,the feasibility of the finite element analysis of temperature for the slide block of rolling- sliding compound bearing is verified.